The Epidemiology and Evolution of Rifampicin Mono Resistant Tuberculosis in Khayelitsha, Cape Town, South Africa - Salaam-Dreyer, Zubeida (Division of Medical Microbiology, 2021)
Background: According to the World Health Organization Global TB report 2018, rifampicin monoresistant tuberculosis (RMR-TB) comprises 22% and 38% of all rifampicin-resistant TB (RR-TB) globally, and within South Africa, respectively. National surveys from South Africa show an increasing proportion of RMR-TB among TB cases compared to multi-drug resistant tuberculosis (MDR-TB) from 2001-02 (0.4% vs 2.9%) to 2012-14 (1.7% vs 2.8%). Data from the 2012-14 survey showed considerable variation in RMR-TB prevalence throughout the nine provinces of South Africa. Despite the above, factors associated with the rise in RMR-TB are unknown; and research is limited. This thesis aims to describe RMR-TB in more detail, by investigating the emergence and transmission of RR-TB strains in Khayelitsha, Western Cape Province, South Africa. This included: conducting a systematic review on temporal trends, transmission and risk factors associated with RMR-TB; describing the overall prevalence of RMR-TB among RR-TB; assessing the relative risk of RMR-TB versus MDR-TB among RRTB patients by HIV status during prior TB treatment; describing the distribution of rpoB mutations among RR-TB strains and assessing minimum inhibitory concentration (MIC) values in RR-TB strains with particular rifampicin-resistance (RIF R) conferring mutations; and investigating potential transmission through whole genome sequence (WGS) derived clusters among RR-TB strains. Methods: Routinely diagnosed RR-TB isolates are stored in a biobank at Stellenbosch University (SU). Clinical data (Médecins sans Frontières and additional data requested from the Western Cape Provincial Health Data Centre), together with stored RR-TB isolates from the biobank across 2013-15 inclusive were used to address research questions in Khayelitsha. To describe the overall prevalence of RMR-TB among all RR-TB over time, epidemiological data from 2008-17 were used. Laboratory techniques (sub-culturing of stored frozen cultures into mycobacterial growth indicator tubes [MGITs] for DNA extraction and quantitative phenotypic DST [q pDST]) involving the handling of live Mycobacterium tuberculosis cultures, were done in a Biosafety Level 3 laboratory at SU. Extracted DNA was sent to the University of Basel in Switzerland for library preparation and whole genome sequencing (WGS) on the Illumina HiSeq. The raw fastq WGS data files of the sequenced DNA were securely transferred to UCT. TB profiler was used to identify RIF R conferring mutations in rpoB and strain lineages. rpoB mutations were classified as high/moderate and minimal confidence in conferring rifampicin-resistance. q pDST (MGIT) was performed for isolates with minimal, moderate and rpoB confidence level mutations that were not classified. q pDST was also performed on isolates found to be rifampicin susceptible TB (RS-TB using WGS) [no RIF R conferring rpoB mutations detected] but were isolated from patients routinely diagnosed with RR-TB. A combination of software packages was used, as well as in-house developed scripts to compile a pipeline for WGS transmission cluster analysis. Computations were performed using facilities provided by UCTs ICTS High Performance Computing (HPC) team. Clusters were identified with Clusterpicker and by generating a single nucleotide polymorphism (SNP) distance matrix (SNP differences found between genomes) using R software; a SNP threshold of 12 was used to suggest recent transmission. Results: i) The overall prevalence of RMR-TB among all RR-TB remained relatively stable (17-31%) with no major temporal trend observed during 2008-17 in Khayelitsha. ii) The proportion of RMR-TB among all RR-TB was significantly higher among patients who were HIV positive during previous TB treatment compared to those who were HIV negative. iii) A high proportion (11%) of discordance was found among RIF R routinely diagnosed RR-TB patients (43% RMR-TB; 57% MDR-TB); resulting from possible mixed infections (43%), false-positive RIF R (18%) or both (39%). iv) The WGS-based DR-TB profile for rpoB mutations were distinctly different between RMR- and MDR-TB strains. The proportion of high/moderate vs minimal confidence levels for rpoB mutations was significantly higher among MDRTB (high confidence rpoB S531L mutation - Lineage 2) than for RMR-TB. v) Among RMR-TB strains, rpoB L511P (described as a disputed mutation, conferring minimal confidence for RIF R or low-level RIF R) was predominantly found among RMR-TB strains compared to MDR-TB strains. All rpoB L511P mutations (including RMR- and MDR-TB) tested phenotypically susceptible to rifampicin with MGIT; causing discrepancies between WGS and q pDST. All RMR-TB strains, including those with rpoB L511P mutations, had no other mutations conferring resistance to any of the other TB drugs. vi) Clustering was higher among MDR-TB strains compared to RMR-TB and more MDR-TB strains were clustered among strains with the rpoB S531L mutation compared to RMR-TB with the same mutation. In contrast, among strains with the rpoB L511P mutation, more RMR-TB strains were clustered compared to no clustering found among MDR-TB strains with the same mutation. Clinical data showed that RMRTB rpoB L511P clusters were due to closely related community acquired or nosocomial transmission; and SNP differences were < 5, suggesting direct transmission between RMR-TB rpoB L511P patients. Conclusion: In Khayelitsha, lower clustering of RMR-TB strains suggests reduced transmission compared to MDR-TB and along with a different rpoB mutation profile, suggests a different evolutionary mechanism of RIF R. Additionally, RMR-TB appears to be associated with HIV positivity during previous TB treatment, suggesting a role for HIV in the generation of RMR-TB. Given the association of rpoB L511P with low-level RIF R among RMR-TB strains, it is possible that different treatment approaches could be effective for these patients, as there are also no clinical trials to optimise treatment of these patients. WGS is beneficial, not only for understanding transmission of RR-TB strains, but also to be used in combination with MIC testing for individualised patient treatment regimens, in order to accurately diagnose RR-TB in future. Recommendations for preventing M.tb transmission; irrespective of HIV status; include early diagnosis and treatment initiation, and implementation of infection control programmes in various settings.